If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (y + -6) + 8 = 0 Reorder the terms: (-6 + y) + 8 = 0 Remove parenthesis around (-6 + y) -6 + y + 8 = 0 Reorder the terms: -6 + 8 + y = 0 Combine like terms: -6 + 8 = 2 2 + y = 0 Solving 2 + y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + y = 0 + -2 Combine like terms: 2 + -2 = 0 0 + y = 0 + -2 y = 0 + -2 Combine like terms: 0 + -2 = -2 y = -2 Simplifying y = -2
| 3x+2=-2y | | 11.333333+0.3333333q=-0.5q+28 | | 11.333333+0.3333333q=-0.5q | | 5x-20=2x-20 | | 2z/7+4=-7 | | z+0.58=-0.27 | | 2k-10/-7 | | y-16=-2(x-4) | | x(2x-92)=3360 | | -3y=-x+17 | | -3y=-x+18 | | 11.8+x-8.2=3.8 | | =16t^2+16t | | ln(x)=1/12 | | x(2x-2)=3360 | | 50k+100=40k+40 | | 4y=-x-31 | | x/8+7=-5 | | -9y=5x+23 | | 2376+3=83+z | | 1.4=-4.9t^2+30t+1.4 | | 2y=7x+18 | | z/7+9=8 | | 2x^2-7x=15-6x | | -3y=-8x+12 | | 150m-75m+43200=45450+150m | | 10x^2+x+48=0 | | (6a+8)(a+4)= | | 23+x=40 | | 2(2x+6)=100 | | 282=n | | 7a-4=3b+5 |